Aplicativo móvil para la gestión de pago de matrícula en la Universidad Nacional de la Amazonía Peruana 2023 - Da Silva Torres, Gonzalo Mauricio (2024)
The management of tuition payment at the National University of the Peruvian Amazon (UNAP) required extensive time, exceeding 24 hours on average for verification and completion, causing inconveniences for students. This study posed the question: How can a mobile application optimize the time for tuition payment management at UNAP? The objective was to develop and evaluate a mobile application to reduce verification and payment times, as well as to measure student satisfaction. The research, with a quantitative approach, pre experimental design, and pre- and post-test, involved a population of 10,432 students enrolled in the 2023-I semester, selecting specific samples for each analysis. The results indicate that the average time for payment verification decreased from 30.02 hours (108,058.22 seconds) to 5.41 seconds, while the average time for making the payment was reduced from 120.32 minutes to 2.49 minutes. These changes were evaluated using a comparison of means, showing statistically significant differences. Additionally, student satisfaction measured by the SUS scale achieved an average score of 87.20, classified as "Acceptable" in terms of usability. In conclusion, the use of the mobile application significantly optimized the payment and verification processes, drastically reducing times and improving the student experience. This approach demonstrates the effectiveness of mobile technologies in transforming administrative processes in higher education.